Faktor Yang Berhubungan dengan Persepsi Masyarakat Terhadap Vaksin Covid-19 Di Dusun Ompoa Kabupaten Bulukumba - Fadillah Khaerunnisa; Fatmah Afrianty Gobel; Nur Ulmy Mahmud; Hasriwiani Habo Abbas; Farihah Muhsanah (Window of Public Health Journal, 2025)
Vaccination is a public health effort considered the most effective and efficient in preventing the transmission of dangerous diseases. The various news reports regarding the COVID-19 vaccine have caused perceptions to emerge among the community. Research objectives: to determine the factors related to public perception of the COVID-19 vaccine in Ompoa Hamlet, Bulukumba Regency. Research Methods: This research is a quantitative study with a cross-sectional approach. Sampling was done using the purposive sampling technique, namely, 212 people, and data analysis was conducted using univariate and bivariate tests using the MS Excel and SPSS programs. The measuring instrument used is a questionnaire. Research results: there is a relationship between age and public perception of the Covid-19 vaccine (p = 0.024 <α = 0.05), there is a relationship between knowledge and public perception of the Covid-19 vaccine (p = 0.000 <α = 0.05), there is a relationship between attitudes and public perception of the Covid-19 vaccine (p = 0.000 <α = 0.05), there is a relationship between the side effects of the Covid-19 vaccine and public perception of the Covid-19 vaccine (p = 0.334> α = 0.05), there is a relationship between a history of comorbid diseases and public perception of the Covid-19 vaccine (p = 0.031 <α = 0.05). Conclusion: There is a relationship between age, knowledge, attitudes, and medical history, and there is no relationship between the side effects of the COVID-19 vaccine and public perception of the COVID-19 vaccine in Ompoa Hamlet, Bulukumba Regency.